2015
DOI: 10.1016/j.jbiotec.2015.06.396
|View full text |Cite
|
Sign up to set email alerts
|

Metagenome changes in the mesophilic biogas-producing community during fermentation of the green alga Scenedesmus obliquus

Abstract: A microalgal biomass offers a potential alternative to the maize silage commonly used in biogas technology. In this study, photoautotrophically grown Scenedesmus obliquus was used as biogas substrate. This microalga has a low C/N ratio of 8.5 relative to the optimum 20-30. A significant increase in the ammonium ion content was not observed. The methane content of the biogas generated from Sc. obliquus proved to be higher than that from maize silage, but the specific biogas yield was lower. Semi-continuous stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 59 publications
2
29
0
Order By: Relevance
“…Methanosaeta remained predominant in the C. vulgaris fed digester, but their relative number of methanogens decreased in time (Supplementary Figure 2). The genus Methanosarcina replaced Methanosaeta in abundance in the case of maize silage and co-digestion as the experiment progressed (Ellis et al, 2012;Wirth et al, 2012Wirth et al, , 2015aPope et al, 2013;Klassen et al, 2016) (Figure 6 and Supplementary Figure 2). In earlier studies, both Methanosarcina and Methanosaeta have been reported to be dominant methanogens (Zamalloa et al, 2012;Gonzalez-Fernandez et al, 2015;Klassen et al, 2016), depending primarily on the actual acetate concentration.…”
Section: The Core Microbial Communitymentioning
confidence: 98%
See 1 more Smart Citation
“…Methanosaeta remained predominant in the C. vulgaris fed digester, but their relative number of methanogens decreased in time (Supplementary Figure 2). The genus Methanosarcina replaced Methanosaeta in abundance in the case of maize silage and co-digestion as the experiment progressed (Ellis et al, 2012;Wirth et al, 2012Wirth et al, , 2015aPope et al, 2013;Klassen et al, 2016) (Figure 6 and Supplementary Figure 2). In earlier studies, both Methanosarcina and Methanosaeta have been reported to be dominant methanogens (Zamalloa et al, 2012;Gonzalez-Fernandez et al, 2015;Klassen et al, 2016), depending primarily on the actual acetate concentration.…”
Section: The Core Microbial Communitymentioning
confidence: 98%
“…Binning uncovered eleven Bacteroidetes genome fragments (Bins 6,7,9,10,13,14,43,44,54,55,and 56) containing genes for hydrolyzing enzymes (Supplementary Table 4). The genera Clostridium and Bacteroides have been also implicated in the efficient deconstruction of microalgal cell wall (Yen and Brune, 2007;Wirth et al, 2015a).…”
Section: The Core Microbial Communitymentioning
confidence: 99%
“…Microbial communities involved in anaerobic digestion processes are highly variable in their composition, which is determined by factors like inoculum source, operational conditions such as temperature, SRT or Organic Loading Rate (OLR), and the type of feedstock used [14]. In this context, little is known about the bacterial consortium capable of degrading Scenedesmus under anaerobic conditions, and this lack of knowledge limits optimization of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Domestication also changed the structure and composition of Archaea. Two distinct methanogen groups, acetoclastic and hydrogenotrophic, play major roles in producing methane (Wirth et al, 2015). Because hydrogenotrophic methanogens are more resistant to toxic substances such as ammonia than acetoclastic methanogens, conditions that favor hydrogenotrophic methanogen domination in AD systems are desirable.…”
Section: Discussionmentioning
confidence: 99%